Diorama Arsip Jogja Potential as a History Learning Resource at Senior High Schools - Vidya Putri Kartini; Amirul Syafiq; Miftahuddin Miftahuddin (Pusat Publikasi Nusantara, 2024)
The Jogja Archives Diorama is a digital diorama which consists of various types of archives, including textual, photo, audiovisual, and oral history, with items sourced from regional, national, and international archives as well as personal collections. This study aims to explore the potential of the Dioram Arsip Jogama as a source of history learning at the high school level with a descriptive qualitative approach. Through field research, the researcher seeks to dig up in-depth information about the relevance of the Jogamar Archive Diogama in the context of historical learning, especially at SMA Negeri 8 Yogyakarta, SMA Prambanan, and SMA Minggir. The research results indicate that (1) the diverse collection at the Digamar Archives is mainly composed of textual and photo archives, and the collection is divided into three categories, including oral history and textual history. (2) The Digamara Archive of Indonesia is relevant to history learning in grades X, XI, and XIII, with the potential to be a learning resource that can support the history learning process. (3) Problem-Based Learning (PBL) is suggested as an effective teaching method to engage students in historical analysis and critical thinking. Future researchers are encouraged to use this study as an a reference for further exploring the utilization of archives as learning resources, especially focusing on expanding the scope of the digamara archive to include more schools and testing different learning models to enhance historical education.